2012
DOI: 10.1007/s12033-012-9568-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Microgravity Rotating Culture System on the Chondrogenic Differentiation of Bone Marrow Mesenchymal Stem Cells

Abstract: We investigated the influence of the microgravity rotating culture system on the chondrogenic differentiation of bone marrow mesenchymal stem cells (MSCs). During chondrogenic induction, MSCs combined with polyglycolic acid (PGA) were cultured by static culture or microgravity rotating culture and chondrocyte formation was confirmed by toluidine blue staining. Furthermore, the mRNA and protein expressions of a specific cartilage extracellular matrix protein (collagen type II and Aggrecan) were evaluated by rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Cell inoculation and sampling in the RCCS group were performed as described by Wu X et al [ 12 ]. Cells were harvested, and cell density was adjusted to 10 5 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell inoculation and sampling in the RCCS group were performed as described by Wu X et al [ 12 ]. Cells were harvested, and cell density was adjusted to 10 5 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…This effect is helpful for the transport of nutrients and the removal of metabolic wastes, thus promoting chondrocyte proliferation and cartilage matrix synthesis [ 10 , 11 ]. Studies have confirmed that RCCS promotes the differentiation of BMSCs into chondrocytes and is conducive to the maintenance of the chondrocyte phenotype and biomechanical characteristics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 An increasing amount of research is focused on the effects of gravity alterations on the physiological processes, but also on the possibility to exploit this stimulus as a potential therapeutic cue. [7][8][9] As an example, improved regeneration of infarcted myocardium has been achieved after injection of stem cells differentiated following …”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the p38 MAPK signal mediates s- μg -induced chondrogenesis of ADSCs. In MSCs cultured during chondrogenic induction in a rotating culture, combined with polyglycolic acid (PGA), mRNA and proteins of collagen type II and aggrecan were significantly more expressed in the s- μg rotating culture group than the static culture group, as reported by Wu et al [25]. Zhang et al [26] described that MSCs spread out in a spindle shape when cultured in normal gravity, while they become unspread and round under s- μg .…”
Section: Mesenchymal Stem Cells and Microgravitymentioning
confidence: 83%